2005
DOI: 10.1111/j.1365-2486.2005.00933.x
|View full text |Cite
|
Sign up to set email alerts
|

Ambient ultraviolet radiation in the Arctic reduces root biomass and alters microbial community composition but has no effects on microbial biomass

Abstract: We assessed the effects of ambient solar ultraviolet (UV) radiation on below-ground parameters in an arctic heath in north-eastern Greenland. We hypothesized that the current UV fluxes would reduce root biomass and mycorrhizal colonization and that these changes would lead to lower soil microbial biomass and altered microbial community composition. These hypotheses were tested on cored soil samples from a UV reduction experiment with three filter treatments (Mylar, 60% UV-B reduction; Lexan, up to 90% UV-B red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 44 publications
4
39
0
Order By: Relevance
“…All these results suggest that the increased UV-B radiation can influence overall dynamics of a root secreted GA that might indirectly influence invasiveness of a noxious weed P. australis. Effects of UV-B on root secretion have previously been documented [11][12][13][14][15] show that UV-B incidences may regulate the root secretion effluxes. To the best of our knowledge no study has reported the effects of UV-B radiation to augmented root derived allelopathy in plants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All these results suggest that the increased UV-B radiation can influence overall dynamics of a root secreted GA that might indirectly influence invasiveness of a noxious weed P. australis. Effects of UV-B on root secretion have previously been documented [11][12][13][14][15] show that UV-B incidences may regulate the root secretion effluxes. To the best of our knowledge no study has reported the effects of UV-B radiation to augmented root derived allelopathy in plants.…”
Section: Discussionmentioning
confidence: 99%
“…UV-B incidence modifies root secretion efflux thus affecting the total dissolved oxygen carbon (DOC) content in the rhizosphere. 11,23 Although most of these studies are species specific, it reveals a trend that UV-B radiations could change the litter or secretion chemistry in plants, leading to changes in rhizospheric microbial abundance. Interestingly, UV radiation has been recognized as a significant cause of photochemical transformation of dissolved organic matter (DOM) in surface waters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The domain Archaea is also resistant to UV-B (Thummes et al, 2007), and there is a general trend of increased species diversity in environments with higher levels of UV-B exposure (Robson et al, 2005). The gram-negative bacterial community in Arctic soils experiences particular environmental stresses and nutrient limitations (Rinnan et al, 2005). Avery et al (2003) conducted a study of the response of the rhizosphere microbial communities associated with populations of Deschampsia antarctica (a native vascular plant from Antarctica), which were exposed to UV-B, and found that radiation not only modified the overall growth of the plant but also the production of secondary metabolites.…”
Section: Uv Radiation (Uvr)mentioning
confidence: 99%